A practitioner's guide to setting up community-based small ruminants breeding programs - International Center for Agricultural Research in the Dry Areas (International Center for Agricultural Research in the Dry Areas, 2021)
Implementers of CBBPs (extensionists, researchers, breeder cooperatives, NGOs staff, members of farmers associations)